Improving Analysis of Risk-Based Maintenance Management Strategies Through Reliability Centered Maintenance. Case Study : Coal Crushing Plant. Central Kalimantan. Indonesia - Widotomo, Gayuh (Universitas PGRI Semarang, 2024)
PT XYZ as a company operating in the coal mining sector has 7 production lines on the in-loading system in its coal crushing plant. In-loading system production line no. 7 is the system that has the lowest mechanical availability, therefore it is necessary to search for a systematic method to obtain an appropriate maintenance mode and not only consider operational aspects but also pay attention to occupational health safety aspects. RCM is a qualitative analysis (which can be developed into quantitative analysis) which formulates maintenance task selection based on safety, environmental and operational considerations. From the results of the FMEA research, it was found that there were 28 failure modes with 6 components of which had an unacceptable risk level and a critical level of